Effect of some Seed Dressings on Germination of Wheat Grain - EL-ZAYYAT, M. M.; SAWHNEY, JAGDEV S.; ABLACK, MUSTAFA; NASHNOOSH, IBRAHIM (The Libyan Journal of Agriculture, 2023)
Wheat grains of cv. Sedi Mesri 1, were treated with different concentrations of Benomyl (Benlate), Quinolate. Triplecar MN and Carboxin (Vitavax)-Thiram mixture (20:40). The treated and untreated grains were germinated at 25°C under controlled conditions for six days. No adverse effect of seed dressing was found on percent germination, speed of germination and the growth of the embryo.